2017
DOI: 10.1104/pp.17.00816
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid Dehydratase Gene Dosage Affects Programmed Cell Death and Immunity

Abstract: Programmed cell death (PCD) is an important form to protect plants from pathogen attack. However, plants must precisely control the PCD process under microbe attacks to avoid detrimental effects. The complexity of how plants balance the defense activation and PCD requires further clarification. Lesion mimic mutants constitute an excellent material to study the crosstalk between them. Here, we identified a (cotton) lesion mimic mutant (), which exhibits necrotic leaf damage and enhanced disease resistance. Map-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 57 publications
(71 reference statements)
2
36
0
Order By: Relevance
“…In agreement with our results, Chai et al. () reported an increase in the level of ROS and H 2 O 2 in Gossypium hirsutum (cotton) lesion mimic mutant ( Ghlmm ), which exhibited an accumulation of δ ‐ALA as a result of low activity of the ALAD enzyme. An increase in methanedicarboxylic aldehyde (MDA) level was also observed in mutant leaves, indicating peroxidation of unsaturated membrane lipids in cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our results, Chai et al. () reported an increase in the level of ROS and H 2 O 2 in Gossypium hirsutum (cotton) lesion mimic mutant ( Ghlmm ), which exhibited an accumulation of δ ‐ALA as a result of low activity of the ALAD enzyme. An increase in methanedicarboxylic aldehyde (MDA) level was also observed in mutant leaves, indicating peroxidation of unsaturated membrane lipids in cells.…”
Section: Discussionsupporting
confidence: 93%
“…An increase in methanedicarboxylic aldehyde (MDA) level was also observed in mutant leaves, indicating peroxidation of unsaturated membrane lipids in cells. Silencing of ALAD in G. hirsutum by the TRV‐based VIGS also resulted in the same phenotype observed in mutant plants and showed an accumulation of δ ‐ALA and H 2 O 2 (Chai et al., ). The mutant plant also accumulated SA and showed high expression levels of pathogenesis‐related genes (PR) and high resistance to Verticillium dahliae infection (Chai et al., ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To detect and quantify the biomass of V. dahliae in cotton seedlings, the first true leaf of cotton plants at 22 dpi was collected for DNA extraction. qPCR was used to quantify the relative amount of fungal DNA (Chai et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Many lesion‐mimic mutants have been reported, and about 40 associated genes have been isolated (Bruggeman et al ., ). Those genes fall into several functional groups, including ‘membrane‐associated protein’ (Büschges et al ., ), ‘ion channel’ (Balague, ), ‘zinc‐finger protein’ (Dietrich et al ., ), ‘porphyrin metabolism’ (Chai et al ., ), and ‘fatty acid metabolism’ (Sun et al ., ). In our study, we found a group of lesion‐mimic mutants that participate in tryptophan synthesis.…”
Section: Discussionmentioning
confidence: 99%